Sketches on history of studying radioactivity and formation of uranium geology in the Central Siberia. Sketch one. Beginnings; Bulletin of the Tomsk Polytechnic University; Vol. 311, № 1 - Domarenko V. A. Victor Alekseevich (Pages of TPU history, 2007)
Заглавие с титульного листа